Exploring ZnO nanostructures with reduced graphene oxide in layer-by-layer films as supercapacitor electrodes for energy storage - Oliveira, Danilo A.; da Silva, Ranilson A. [UNESP]; Orlandi, Marcelo O. [UNESP]; Siqueira, José R. (Springer Nature, 2022)
Intense research has been done in the field of clean and renewable sources and energy storage. Supercapacitors are a promising technology for portable and wearable electronic systems. The combination of metal oxides with graphene is attractive to form nanocomposite materials to achieve energy storage devices with enhanced properties. Here, we study the fabrication of nanofilms as supercapacitor electrodes using two nanostructures of zinc oxide, tetrapod [ZnO(t)] and star [ZnO(s)], complexed with reduced graphene oxide (rGO) and arranged with poly(allylamine hydrochloride) (PAH), by using the layer-by-layer (LbL) technique on a flexible indium–tin–oxide (ITO) electrode. The morphology of both ZnO-based films was investigated by scanning electron microscopy, which revealed the incorporation of ZnO with rGO and led the formation of nanostructured films with high surface area in two distinct morphologies. Cyclic voltammetry and galvanostatic charge–discharge measurements exhibit profile curves of a supercapacitor-based double-layer energy storage mechanism with high cycling stability over 10,000 cycles. The highest capacitance was achieved for a 20-bilayer LbL film at a 1 mV/s and 1 A/g with values of ca. 5 mF/cm2 and 140 F/g for ZnO(t)-based film and of ca. 19 mF/cm2 and 90 F/g for ZnO(s)-based film. Also, films with ZnO(t) presented energy and power densities of ca. 9.5 Wh/kg and 207 W/kg, respectively, while the same parameters exhibited values of ca. 6.0 Wh/kg and 130 W/kg for films with ZnO(s). Our findings indicate that nanofilms-based ZnO-rGO exhibit electrocapacitive properties that permits to be further investigated for energy storage nanostructured systems.